Innovative Approaches in Integrated Assessment and Management of Residential Real Estate - B. A., Suyunov. (European Journal of Life Safety and Stability (2660-9630), 2021)
The article analyzes the economic foundations of the formation of the market value of residential real estate. The study describes the main factors affecting the value of real estate in Samarkand, analyzes the housing needs of the population, analyzes the primary and secondary real estate market, and analyzes the stages of property obsolescence. The final section provides recommendations for improving real estate valuation.